Laser therapy for genital lichen sclerosus: A systematic review of the current evidence base - F. Tasker; L. Kirby; D. J. C. Grindlay; F. Lewis; R. C. Simpson (Wiley, 2021)
Abstract Background Lichen sclerosus (LS) is a chronic, inflammatory dermatosis. Initial treatment with superpotent topical corticosteroids is the accepted and evidence‐based first‐line therapy. For those who do not respond after exclusion of other potentiating factors, the best second‐line therapy is unclear. Laser therapy is an emerging treatment for genital LS and despite uncertain efficacy its use is gaining popularity in the private sector. Objectives We aimed to review the effectiveness of laser therapy for genital LS in men, women and children. Methods We conducted a systematic review of all primary studies reporting the use of laser in genital LS. Ovid MEDLINE, PubMed, Ovid Embase, Cochrane CENTRAL, Web of Science, CINAHL and PsycINFO were searched from inception to February 2021. The quality of the studies was assessed using the revised Cochrane risk‐of‐bias tool for randomized trials, ROBINS‐I tool for non‐randomized trials and Joanna Briggs Institute checklist for case studies. Results A total of 24 studies, involving 616 adults, met inclusion criteria. These were six randomized controlled trials (RCTs), one non‐randomized trial, nine single arm trials and eight case series. Where assessed, most studies suggest that laser therapy in patients with LS may improve symptoms, clinical signs, quality of life and sexual function. However, results were highly heterogeneous and methodological quality was very low, therefore meta‐analysis was not possible. Conclusions There is poor evidence to support the use of laser therapy for genital LS at present. Effectiveness of laser needs to be robustly investigated in well‐conducted RCTs.